2000
DOI: 10.1159/000026130
|View full text |Cite
|
Sign up to set email alerts
|

Causal Factors and Management Options of Infertility in Kuwait

Abstract: Objective: To determine the main causes and management options of infertility in Kuwait. Methodology: Clinical evaluation, hormone profile of LH, FSH, prolactin and testosterone and midluteal phase progesterone, tubal patency tests, semen analysis and antisperm antibodies were assessed. Treatment included medical and surgical induction of ovulation. Male factor infertility was treated with antibiotics and immunosuppression when indicated, and empirically with antioxidants. Results: The main cause of female inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
(19 reference statements)
0
11
1
Order By: Relevance
“…17 However, the mean age of women in this study was higher than what was reported in neighboring countries, and the Eastern Asian countries. In Kuwait, the mean age was 29.9+ 5.4 years, 18 while it was 29 + 6.0 years in Iran and 25.9 + 4.18 years in India. 19,20 The causes may be the lower educational attainment, cost issues and most importantly the delay in establishing of fertility and ART centers in our country because of the wars and civil strife for decades with minimal infrastructure and organizations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, the mean age of women in this study was higher than what was reported in neighboring countries, and the Eastern Asian countries. In Kuwait, the mean age was 29.9+ 5.4 years, 18 while it was 29 + 6.0 years in Iran and 25.9 + 4.18 years in India. 19,20 The causes may be the lower educational attainment, cost issues and most importantly the delay in establishing of fertility and ART centers in our country because of the wars and civil strife for decades with minimal infrastructure and organizations.…”
Section: Resultsmentioning
confidence: 99%
“…21 A meta-analysis study in Iran reported that 78.4% of couples had primary and 21.6% had secondary fertility problems. 1 In Kuwait, 63% of the infertile women had primary infertility and 37% had secondary infertility, 18 and in Egypt the rates of primary and secondary infertility were 70.7% and 29.3% respectively among infertile couples. 22 The most comprehensive study of infertility was that of the WHO on 5800 infertile couples seeking help at 33 medical centers in 22 developed and developing countries, which revealed that the majority of infertile couples around the world suffer from primary infertility.…”
Section: Resultsmentioning
confidence: 99%
“…The present study demonstrated ovarian dysfunction as the most common cause in female infertility of which anovulatory menstrual cycle (60%) topped the list. Anovulation is also a common factor in Kuwait (25%) 8 and Iran (28.8%) 17 . Our study found women with bilateral tubal occlusion (8%) and pelvic adhesions (24%), for many women in developing countries especially in Sub-Saharan African countries suffer infertility resulting from untreated PID, a sequel of a STI or other reproductive tract infection 3,19 .…”
Section: Resultsmentioning
confidence: 99%
“…The causes of infertility vary from country to country and in the different cultural, environmental and socioeconomic groups 7 . For an example, hypothalamic -pituitary-ovarian axis disorders with anovulation are the commonest causal factors of infertility in Kuwait 8 . On the other hand, tubal factor infertility related to infection is more common in Africa, South America and India 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation